The Infection of COVID-19 among Health Care Workers in Dharmais Cancer Hospital - Mutiara Adelina; Fifi Dwijayanti (Indonesian Journal of Cancer, 2021)
Infectious diseases are one of the biggest threats to humans. Currently, the world is in the outbreak condition causes of the COVID-19 virus which is started from Wuhan, China in December 2019. This disease was spread out rapidly throughout the World and was announced as a pandemic by the World Health Organization (WHO) on March 11, 2020(1). The infected number of SARS-CoV-2 was over 84 million people and caused over 1 million death cases in the worldwide. Indonesia had more than 800.000 infectious cases and 23.000 of death cases with the highest cases in Jakarta (2). This virus can be transmitted by two ways, such as direct contact (cough, sneeze, and droplet inhalation) and contact transmission (contact with oral, nasal, and eye mucous membranes) of person with COVID-19 (3). The current COVID-19 pandemic makes various challenges in prevention and control of infections in hospitals. Health care workers (HCWs) have been providing care to suspected, probable or confirmed COVID-19 patients that make them in high-risk condition. Several study indicated that many HCWs have been infected with SARS-CoV-2 in many hospitals worldwide (4)(5)(6).